Cytokinin-induced mRNAs in cultured soybean cells. - Crowell, D N (1990)
We have isolated 20 cDNA clones for which the corresponding mRNAs accumulate 2- to 20-fold within 4 hr of cytokinin addition to cytokinin-starved soybean suspension cultures. These changes in mRNA levels precede the greening and cell growth induced by cytokinin in this system. Treatment with cycloheximide before cytokinin addition enhances the accumulation of these messages. In addition, the abundance of these mRNAs is influenced by auxin. We demonstrate that the mRNAs corresponding to the cDNAs in this collection display a variety of patterns of accumulation in the tissues of an intact plant. We also show that different cytokinins induce similar increases in message levels. However, analogs of cytokinin that are much less active in bioassays induce lower levels of message accumulation. Sequence analyses indicate that two of the cDNAs correspond to ribosomal protein genes. The remaining cDNAs are likely to represent previously undiscovered genes that function early in the initiation of plant cell growth and/or chloroplast development.